Pemberdayaan Perekonomian Masyarakat melalui Sistem Koperasi Syariah di Desa Mendalo Indah - Kuswanto Kuswanto; Irzal Anderson; Refnida Refnida (Universitas Mathla'ul Anwar Banten, 2021)
COMMUNITY ECONOMIC EMPOWERMENT THROUGH THE SHARIA COOPERATIVE SYSTEM IN THE VILLAGE OF MENDALO INDAH. The weakening of the community economy is due to the fact that resource management is still partial and not yet systematic. Massive awareness is needed to build a strong economy so that it can face market competition. The purpose of this service is to realize the economic independence of the community through strengthening capital, increasing expertise and strengthening institutions. Empowerment of the community's economy is carried out by disseminating the Sharia Cooperative system, mentoring community financial management and processing businesses based on the syariah cooperative system. The object of service is the community of Arza Griya Mandiri housing in Mendalo Indah Village who are members of a business group. Through community service activities, community potential empowerment is carried out through a syariah cooperative system. From this activity, community businesses are formed which are managed based on a sharia cooperative system consisting of 17 members and having two business units in the field of trade and payment services for waste transportation. By raising funds from members 'savings, it is able to facilitate the development of members' businesses through capital loans. With the existence of business development based on the sharia cooperative system, the community gets additional income from the SHU share.